ANALISIS PENGEMBALIAN KREDIT MIKRO PRODUK KREDIT ANGSURAN SISTEM FIDUSIA (KREASI) (Pada Cabang Bisnis Mikro Laskar Melayu Kanwil II PT Pegadaian Pekanbaru) - Sundari "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The study aims to find out the return of micro credit on fiduaciary system installment credit products (KREASI) at the micro business branch of the Malayu Laskar Kanwil II PT Pegadaian Pekanbaru in the 2014-2018 period. Which is measured using the Gutman scale. Type of research conducted in the from of secondary data, where the data is from financial statements. Data collection methods used in this study were questionnaire and interview. Standard data analysis using a mix methods research approach or mix methods, which describe the conditions of micro credit repayment rates on installments of the fiduciary credit system (KREASI) and explain the factors that cause credit returns are not in accordance with the existing targets and regulations. Based on the results of data analysis of micro credit returns of fiduciary installment credit products (KREASI) in the micro business unit of the Malayu Laskar Kanwil II PT Pegadaian Pekanbaru. Conclude that on special attention credit, doubtful credit and bad credit, getting a bad or low yield with a percentage of less that 50%, whereas for current credit and substandard credit can be categorized quite well because it has a percentage above 70%. Of the overall results of data analysis on micro installments of the fiduciary credit system (KREASI) on the Malayu Laskar Kanwil II PT Pegadaian Pekanbaru in the low category.Keywords: Analysis, credit return, KREASI and CBM Malayu Laskar.